UJI TOKSISITAS EKSTRAK ETANOL DAUN KEMANGI (OCINUM SANCTUM L.) TERHADAP LARVA UDANG (ARTEMIA SALINA L.) DENGAN METODE BSLT (BRINE SHRIMP LETHALITY TEST) - Alfin Surya; Rosa Murwindra; M Syahrul Fiki (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2022)
Basil is known to contain chemical flavonoids, namely orientin and vicenin where these two compounds can protect the body from the effects of radiation.The purpose of this study was to determine the toxicity of the ethanol extract of basil leaves (Ocimum Scantum Linn). Artemia salina Leach larvae using the Brine Shrimp lethality Test (BSLT) method. This study used 3 concentrations, each of which was carried out in triples. The concentrations are 1000 ppm, 100 ppm, 10 ppm. 90 Artemia salina Leach larvae were used. Then observations were made for 24 hours. Then counted the number of shrimp larvae that died after 24 hours. The results were calculated by probit analysis and calculated LC50, obtained LC50 = 21.0523 ppm. So it can be concluded that basil leaves have toxic potential. Because the value of LC50 < 1000 ppm.